HAK-HAK MASYARAKAT ADAT DALAM PENGELOLAAN LINGKUNGAN DALAM KERANGKA HUKUM UNTUKPERLINDUNGAN PENGETAHUAN EKOLOGI TRADISIONAL - Irdini, Kesuma; Defi, Liza Mutiara (JUSTITIABLE - Jurnal Hukum, 2025)
ABSTRACT Indigenous peoples have an important role in environmental management through traditional ecological knowledge passed down across generations. However, legal recognition of their rights still faces serious challenges, such as the slow process of recognizing customary areas, sectoral policy conflicts, and the absence of legal protection for traditional knowledge. This study uses a normative legal study method with a qualitative approach based on literature studies. The results of the analysis show that although there is recognition in the constitution and several sectoral regulations, the implementation is still partial and has not been effective in protecting the rights of indigenous peoples. For this reason, it is necessary to strengthen the law through regulatory harmonization, acceleration of recognition of customary areas, enactment of special laws, and mechanisms for protecting traditional ecological knowledge as communal wealth. These steps are important to support social justice and environmental sustainability in Indonesia. Keywords: Indigenous Peoples, Environment, Traditional Knowledge